2022
DOI: 10.1038/s41375-022-01726-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo PDX CRISPR/Cas9 screens reveal mutual therapeutic targets to overcome heterogeneous acquired chemo-resistance

Abstract: Resistance towards cancer treatment represents a major clinical obstacle, preventing cure of cancer patients. To gain mechanistic insights, we developed a model for acquired resistance to chemotherapy by treating mice carrying patient derived xenografts (PDX) of acute lymphoblastic leukemia with widely-used cytotoxic drugs for 18 consecutive weeks. In two distinct PDX samples, tumors initially responded to treatment, until stable disease and eventually tumor re-growth evolved under therapy, at highly similar k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Enrichment analysis suggested that these target genes were associated with cell adhesion-related biological processes (Fig. 4e ), suggesting potential dysregulated interaction of leukemia cells and mesenchymal stromal cells in the bone marrow microenvironment, which was previously shown to be associated with chemoresistance of leukemia cells 34 , 35 .…”
Section: Resultsmentioning
confidence: 77%
“…Enrichment analysis suggested that these target genes were associated with cell adhesion-related biological processes (Fig. 4e ), suggesting potential dysregulated interaction of leukemia cells and mesenchymal stromal cells in the bone marrow microenvironment, which was previously shown to be associated with chemoresistance of leukemia cells 34 , 35 .…”
Section: Resultsmentioning
confidence: 77%
“…They identified BCL2 and successfully recovered the tumor sensitivity toward chemotherapy. 124 Interestingly, Carlet et al used Cre-ERT2 inducible RNAi to mimic anti-cancer therapy and silence genes in PDX models, which combined the properties of the Cre-loxP system and RNAi techniques. 125 A DNA barcode sequence is a type of unique sequence which can track the exact cells or components that carry it.…”
Section: Novel Support Technologies For the Pdx Modelmentioning
confidence: 99%
“…Notably, recent studies by Bahrami et al. 168 , 169 and Wirth et al. 168 , 169 have demonstrated the feasibility and potency of in vivo CRISPR-Cas9 functional screening in models of AML and chemoresistance, unveiling crucial genes such as BCL2 , BRIP1 , and COPS2 that govern therapeutic outcomes.…”
Section: Synergistic Integration Of Cutting-edge Technologies With Cr...mentioning
confidence: 99%